2021
DOI: 10.3390/ijms222011214
|View full text |Cite
|
Sign up to set email alerts
|

Olive Varieties under UV-B Stress Show Distinct Responses in Terms of Antioxidant Machinery and Isoform/Activity of RubisCO

Abstract: In recent decades, atmospheric pollution led to a progressive reduction of the ozone layer with a consequent increase in UV-B radiation. Despite the high adaptation of olive trees to the Mediterranean environment, the progressive increase of UV-B radiation is a risk factor for olive tree cultivation. It is therefore necessary to understand how high levels of UV-B radiation affect olive plants and to identify olive varieties which are better adapted. In this study we analyzed two Italian olive varieties subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
(104 reference statements)
2
14
0
Order By: Relevance
“…This suggested that the UV-B stress response was weaker in Olivastra Seggianese, and it is possible this variety was unable to engage the same defense mechanisms as Giarraffa, based on readjustments of the levels of the fatty acids. These results aligned with our previous work, in which lipid peroxidation was only noticeable in the Olivastra Seggianese variety (particularly from T2 to T8) [ 24 ]. The absence of variations in lipid peroxidation [ 24 ] in stressed Giarraffa plants could be related to the higher palmitic, α-linolenic, and stearic acid contents found in these plants.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This suggested that the UV-B stress response was weaker in Olivastra Seggianese, and it is possible this variety was unable to engage the same defense mechanisms as Giarraffa, based on readjustments of the levels of the fatty acids. These results aligned with our previous work, in which lipid peroxidation was only noticeable in the Olivastra Seggianese variety (particularly from T2 to T8) [ 24 ]. The absence of variations in lipid peroxidation [ 24 ] in stressed Giarraffa plants could be related to the higher palmitic, α-linolenic, and stearic acid contents found in these plants.…”
Section: Discussionsupporting
confidence: 92%
“…These results aligned with our previous work, in which lipid peroxidation was only noticeable in the Olivastra Seggianese variety (particularly from T2 to T8) [ 24 ]. The absence of variations in lipid peroxidation [ 24 ] in stressed Giarraffa plants could be related to the higher palmitic, α-linolenic, and stearic acid contents found in these plants. Indeed, fatty acids have been described as constitutive elements of complex lipids, but several studies also suggested their direct involvement in abiotic and biotic responses to stress in plants [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is assumed that upon stress modifications can generate RubisCO isoforms that are better suited to cope with a demanding situation. In support of this hypothesis, similar work on olive leaves subjected to UV-B stress [84] and a paper on Micro-Tom leaves subjected to heat stress [85] can be cited. In both cases, the stress treatment altered the profile of RuBisCO isoforms resulting in a more targeted use of isoforms, those most capable of functioning in the altered environmental conditions.…”
Section: Pisanello Cultivar Exhibits the Most Consistent Increase In ...mentioning
confidence: 83%
“…This antibody was purified from human HeLa cells. It recognizes protein homologues in plants and its efficiency has been confirmed in Citrus L. and pepper plants [106] as well as in leaves of olive trees [84].…”
mentioning
confidence: 91%